Pengaruh Penerapan Model Pembelajaran Cooperative Learning Tipe Stad Terhadap Hasil Belajar Siswa Kelas X SMA Negeri 1 Rantau Selatan - Eka Putri Damayanti Siagian; Syahraini Ritonga; Muhammad Rusli (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
This study aims to determine how the effect of the application of the STAD type cooperative learning model on the learning outcomes of class X students of SMA Negeri 1 Rantau Selatan. This study used 2 classes, namely experimental and control classes, the experimental class, namely class X-4, was taught using the STAD type cooperative learning method and the control class, namely class X-1, was taught by the lecture method, which only asked students to pay attention to the material provided by the teacher. Data collection was carried out through a test form, the number of test forms in the form of 30 questions. Data analysis used the t-test statistical test to determine the difference in learning outcomes between the two groups. The results showed that there was a significant difference between the learning outcomes of students taught with the STAD type cooperative learning model. The experimental class students showed better understanding, the STAD type cooperative learning model was proven effective in student learning outcomes. The average pre-test score of the experimental class was 82.42 and increased to 92.37 post test scores, showing an increase of. While the pre-test value of the control class that did not use the STAD type cooperative learning model only increased from 87.17 to 88.45, showing an increase of. The results of the t-count hypothesis 4.13> t-table 2.000 then H0 is rejected and Ha is accepted. Rejection of H0 indicates that there is a significant difference between the post-test scores of experimental and control class students.